An overview of the impact of arab civilizaton on yoruba culture in Nigeria (2023)
Nigeria was a land where idol worship marked the religious life of the inhabitants. With the advent of Islam which came with its civilization, Nigerians’ faith, rituals, rites, practices and customs changed and impacted the Nigerian culture. Invariably, the contact of the Arabs with the people of Yorubaland in Nigeria brought about a new era in their beliefs. The Arabs who were mainly Muslims and with the focus to spread Islam preached assiduously against the syncretic religious practices of the Yoruba in the Southwestern region of Nigeria. There is no gainsaying the fact that every religion has its own unique identity characterized by traditions, values and norms that make it stand out. Over the centuries, we have observed that the southwestern Nigeria culture is gradually fading away as we adopt Arab civilization and this persists as days go by. The Arab civilization has influenced the Yoruba culture in different domains. Some of the impacts are noticeable in our education, language, borrowing, social activities, entertainment, traditional settings, marriage, naming, burial and funeral rites and widowhood. This paper employs historical method which attempts to examine how Arab civilization influenced Yoruba culture in the aforementioned domains including religion and devotional rites. It is our hope that some aspects of Yoruba Culture that are not inimical to Islamic teachings would be preserved to avoid becoming moribund.